2013
DOI: 10.1136/bmjqs-2012-001734
|View full text |Cite
|
Sign up to set email alerts
|

Staffing and resource adequacy strongly related to RNs’ assessment of patient safety: a national study of RNs working in acute-care hospitals in Sweden

Abstract: IntroductionAlthough registered nurses (RNs) are central in patient care, we have not found prior research that specifically addresses how RNs assess the safety of patient care at their workplace and how factors in RNs’ work environment are related to their assessments. This study aims to address these issues.Methods9236 RNs working with inpatient care in 79 acute-care hospitals in Sweden completed a national population-based survey, including Practice Environment Scale of the Nursing Work Index—Revised and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 35 publications
5
79
0
4
Order By: Relevance
“…Likewise, the inverse significant association (p<0.01) found between the workload and the level of satisfaction of the patients with the care received by the nursing team is consistent with the results of other studies, which indicated that higher numbers of patients assigned to the nursing team decrease patient satisfaction and that the restriction or reduction of nursing staff has a negative repercussion on patients' and professionals' perception of safety in care environments (4)(5)(23)(24) . Despite the differences in context, working hours, professional training and others, studies in different countries indicated that the increase in the number of nurses and nursing hours in patient care, as well as a higher proportion of nurses in teams composed also by professionals with a vocational education can improve quality and safety outcomes for patients in hospitals.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, the inverse significant association (p<0.01) found between the workload and the level of satisfaction of the patients with the care received by the nursing team is consistent with the results of other studies, which indicated that higher numbers of patients assigned to the nursing team decrease patient satisfaction and that the restriction or reduction of nursing staff has a negative repercussion on patients' and professionals' perception of safety in care environments (4)(5)(23)(24) . Despite the differences in context, working hours, professional training and others, studies in different countries indicated that the increase in the number of nurses and nursing hours in patient care, as well as a higher proportion of nurses in teams composed also by professionals with a vocational education can improve quality and safety outcomes for patients in hospitals.…”
Section: Discussionsupporting
confidence: 89%
“…When closer involvement with direct patient care occurs, assessment becomes more assertive; and, when human capital and resources are adequate, there is a better perception about patient safety. (18) The complexity of interventions associated with intense specialization and the transformations that occur in healthcare work imposes a coordinated and integrated approach among various professionals to meet the dimensions of human care. The multidisciplinary team meetings stand out as a practice that improve collaboration in the therapeutic plan, from the perspective of comprehensiveness and interdisciplinary attitude.…”
Section: Discussionmentioning
confidence: 99%
“…A favorable working environment increases the interception of medication errors in intensive care (9) . The relationship between a positive working environment and the satisfaction and retention of nurses was also demonstrated (10)(11) , as well as the safety of clients (12)(13) . In contrast, when the work environment is not favorable, the lack of satisfaction of nurses, the burnout syndrome, emotional exhaustion and intention to leave the place of work/service are observed (14)(15)(16)(17)(18)(19) .…”
Section: Study Of Adaptation and Validation Of The Practice Environmementioning
confidence: 96%